E-Magazine Based on Augmented Reality Digestive as Digital Learning Media for Learning Interest - Zulfarina, Zulfarina; Syafii, Wan; Putri, Deka Gusnia (Universitas Pendidikan Ganesha, 2021)
Currently, the obstacles faced in learning process are found to be low student interest in learning. The main factor contributing to low student interest in learning is influenced by the lack of variety of learning media used by teachers in schools. The use of augmented reality (AR) in education is classified as an important research topic, although it is still being studied in its early stages. The purpose of this research was to develop learning media using e-magazine based on an AR to increase students' interest in learning. The developed e-magazine was carried out using model of ADDIE (analysis, design, development, implementation and evaluation). Parameters in this study was focused on the quality of e-magazine and students’ interest in learning. Testing students' interest in learning was conducted by using a questionnaire and given directly to students. The experiments were carried out in the control class consisting of 36 students and the experimental class consisting of 36 students. Results of the study found that the development of AR-based e-magazines were obtained in relatively good category. This value was supported by the validation value found in the very valid category. Analysis on the didactic, constructive and technical aspects were obtained a score of 3,82, 3,85 and 3.78, respectively, with a very valid category. The results also showed that the use of AR-based e-magazines could be increased students' interest in learning and students' interest in learning was obtained at a value of 0.342 in the high category. Thus, the use of AR-based e-magazines as digital learning media can be used in the learning process.